PENYULUHAN TENTANG HUKUM PERLINDUNGAN ANAK - Sukirman Sukirman (Asian Journal of Innovation and Entrepreneurship, 2014)
Dusun Tumut, Jrakah Village, District Selo, Boyolali. People's knowledge of thelaw is still low. Especially for parents and adults about children  protection laws, someeven do not know at all. And also that a child who has been and should be theresponsibility of the parents. Many children are being treated appropriately, for examplechildren aged 6 years has been working hard to drudge for the money. And they also getmarried under age, there is even a 5 th grader who was ready to be married. Withcounseling was given to community child protection laws to put more effort and moreaware, opening the eyes and hearts to break the silence, and helps when there are casesof violence against children that occurred around him.